Dual RNA-Seq Analysis of the Interaction Between Edible Fungus Morchella sextelata and Its Pathogenic Fungus Paecilomyces penicillatus Uncovers the Candidate Defense and Pathogenic Factors - Yu, Yang; Tan, Hao; Liu, Tianhai; Liu, Lixu; Tang, Jie; Peng, Weihong (Frontiers in Microbiology, 2021)
Morels (Morchella spp.) are economically important mushrooms cultivated in many countries. However, their production and quality are hindered by white mold disease because of Paecilomyces penicillatus infection. In this study, we aimed to understand the genetic mechanisms of interactions between P. penicillatus and Morchella. M. sextelata, the most prevalent species of Morchella in China, was inoculated with P. penicillatus; then, the expression profiles of both fungi were determined simultaneously at 3 and 6 days post-inoculation (dpi) using a dual RNA-Seq approach. A total of 460 and 313 differentially expressed genes (DEGs) were identified in P. penicillatus and M. sextelata, respectively. The CAZymes of β-glucanases and mannanases, as well as subtilase family, were upregulated in P. penicillatus, which might be involved in the degradation of M. sextelata cell walls. Chitin recognition protein, caffeine-induced death protein, and putative apoptosis-inducing protein were upregulated, while cyclin was downregulated in infected M. sextelata. This indicates that P. penicillatus could trigger programmed cell death in M. sextelata after infection. Laccase-2, tyrosinases, and cytochrome P450s were also upregulated in M. sextelata. The increased expression levels of these genes suggest that M. sextelata could detoxify the P. penicillatus toxins and also form a melanin barrier against P. penicillatus invasion. The potential pathogenic mechanisms of P. penicillatus on M. sextelata and the defense mechanisms of M. sextelata against P. penicillatus were well described.